Non-bossy social classifcation - Dinko Dimitrov; Clemens Puppe (Fondazione Eni Enrico Mattei (FEEM), 2009)
We consider the problem of how societies should be partitioned into classes if individuals express their views about who should be put with whom in the same class. A non-bossiness condition makes the social aggregator dependent only on those cells of the individual partitions the society members classify themselves in. This information is used to construct for each profile of views an opinion graph. By means of natural sovereignty and liberalism requirements, we characterize the non-bossy aggregators generating partitions in which the social classes are refinements of the connected components in the opinion graph.
Keywords: D71; 330; Social Aggregation; Group Identity; Liberalism; Non-bossiness; Soziale Schicht; Meinung; Soziale Rolle; Aggregation; Public Choice